2007
DOI: 10.1001/archsurg.142.11.1043
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of P-POSSUM and Cr-POSSUM Scores in Patients Undergoing Colorectal Cancer Resection

Abstract: at our institution were enrolled in the study.Main Outcome Measures: P-POSSUM and Cr-POSSUM scores were calculated for each patient. Inhospital mortality rate and number of deaths within 30 days after surgery were recorded. The ratio of observed to expected deaths was calculated for each analysis.Results: The P-POSSUM system underpredicted mortality by 25%, with no significant difference between the predicted and observed values (P=.96). The observed to expected ratio for Cr-POSSUM was 1.11, with no significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
1
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 13 publications
(24 reference statements)
0
34
1
2
Order By: Relevance
“…The previous studies reported that AUCs of ACPGBI were 0.775 and 0.701 in colorectal carcinoma surgery, 7,8 which are similar to our data. AUCs of CR-POSSUM were reported to be 0.59 -0.69, 8,27 which seems to be lower than the current data (0.78). These models probably fail to achieve high discriminatory power by reducing the number of variables.…”
Section: Discussioncontrasting
confidence: 94%
“…The previous studies reported that AUCs of ACPGBI were 0.775 and 0.701 in colorectal carcinoma surgery, 7,8 which are similar to our data. AUCs of CR-POSSUM were reported to be 0.59 -0.69, 8,27 which seems to be lower than the current data (0.78). These models probably fail to achieve high discriminatory power by reducing the number of variables.…”
Section: Discussioncontrasting
confidence: 94%
“…The majority of studies (14/19) reported death rates as 30-day mortality while four studies reported in-hospital rates. In the study 38 that reported both, the 30-day figure was used in the current review. (Table 3) The operative and pathological details of the study populations are summarised in Table 4.…”
Section: Studies Included In the Mortality Analysismentioning
confidence: 99%
“…However, P-POSSUM has no morbidity prediction equation, as a result of the original authors' lack of confidence in the reporting of perioperative complications 59. Subsequent studies have shown P-POSSUM to both over-predict54 64 and under-predict mortality48 61 65 in different settings.…”
Section: Generic Morbidity and Mortality: Perioperative Risk Factorsmentioning
confidence: 99%